The Role of Nurses in the Prevention of Type 2 Diabetes Mellitus Through Healthy Lifestyle Education - Khusnul Khotimah; Wiwin Ramadhani; Janiva Caprianti; Tri Andela (Perkumpulan Dosen Muda Bengkulu, 2026)
Introduction: Type 2 Diabetes Mellitus (T2DM) is a non-communicable disease with a continuously increasing prevalence in Indonesia, reaching 10.9% in 2023. Nurses as frontline health workers have a strategic role in T2DM prevention. Problem: This study aimed to analyze the effectiveness of the nurse's role in T2DM prevention through a structured healthy lifestyle education program in high-risk groups. Method: This study used a quasi-experimental design with a pre-test post-test control group design. A sample of 120 respondents was divided into an intervention group (n=60) and a control group (n=60) at the Bandung City Health Center in 2025. The intervention was a 12-week structured healthy lifestyle education program covering healthy eating, physical activity, stress management, and self-monitoring, delivered by certified diabetes educator nurses. Result and Discussion: The results showed significant differences between groups in fasting blood glucose levels (p=0.001), body mass index (BMI) (p=0.003), knowledge level (p=0.000), and healthy lifestyle behavior (p=0.000). The intervention group showed a mean GDP decrease of 18.4 mg/dL and a BMI decrease of 1.2 kg/m² with significant improvement in knowledge scores. Conclusion: A structured healthy lifestyle education program delivered by nurses is proven effective in preventing T2DM progression in high-risk groups and can serve as a leading intervention model in primary health care facilities.